T V C Â M A R A D E B A U R U PAPEL SOCIAL DO CANAL LEGISLATIVO E SUAS RELAÇÕES COM A COMUNIDADE LOCAL - Monteiro, Carlos Jorge Barros (2004)
This research analyses the TV CÂMARA, a legislative channel of Bauru, a city located in São Paulo, Brazil. Its purpouse is based on a search for the channel s uses, analisyng the programations contents, the process of production and transmition, the social contributions on the contruction of citizen s conscience and finally, its acception by the viewer. The medotological procedures included the participant observation, consisted in follow day by day the TV s activities from March 2002 from February 2003, and July 2003. The documental research had given several informations about the strategies and interviews, which permited the knowledge about comunity participation in the propgrams and the perception about the role of the channel in the city. The fact is that TV CÂMARA has been increasing the options in the local TV broadcasting. The city viewers can see themselves watching the legislative programation. Nevertheless the channel needs to set its existence in the communication field. The society participation can be increased with new programs and more directly, through the guidelines organization. The most important thing is: the legislative channel is a public instrument that must be used by the local population.